O trabalho entre a necessidade e a liberdade: ontologia e emancipação na tese do livro III de O Capital, de Karl Marx - Todai Júnior, Wanderley (2012)
This dissertation aims think about the historic-ontologic content, contained in the relation between the realm of necessity and the realm of freedom, exposed by Karl Marx in book three of his work The Capital. Search examine their fundamental relations in the historical processes that creates social being, according as the being of freedom, as Marx says, have be sought in your own "root". Verifies that the work activity appears, in this historic processuality, as constitutive, but too formed in own jump that give origin to being social, containing insuperable determinations of development of freedom face to necessity. This way, comes up divers activities that are not work activities, but, keeping it how preponderant moments for who have to answer realm necessity , are activities that make feed the individual creativity and define the own purposes realm of freedom. Marx demonstrated that capitalist social relations are boosters the productive forces, expanding unprecedented the capacities and possibilities for to construction of a realm of universal freedom, but their antagonisms effectively tends to turn in realm of necessity. Only overcoming the capitalism for a upper economic formation can accomplish the possibilities of freedom created by him